2022
DOI: 10.32604/cmc.2022.017701
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Deep Learning Framework for Fruits Diseases Classification

Abstract: Agriculture has been an important research area in the field of image processing for the last five years. Diseases affect the quality and quantity of fruits, thereby disrupting the economy of a country. Many computerized techniques have been introduced for detecting and recognizing fruit diseases. However, some issues remain to be addressed, such as irrelevant features and the dimensionality of feature vectors, which increase the computational time of the system. Herein, we propose an integrated deep learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Although their suggested CNN frameworks [22,25] are resilient to class diversity in plant diseases, these models failed to detect plant infections at an early stage. Tariq et al [30] suggested a hybrid framework for plant infection classification. They utilized the ResNet-50 [39] deep learning model for training.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Although their suggested CNN frameworks [22,25] are resilient to class diversity in plant diseases, these models failed to detect plant infections at an early stage. Tariq et al [30] suggested a hybrid framework for plant infection classification. They utilized the ResNet-50 [39] deep learning model for training.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Figure 7 corresponds to the combined confusion matrices for all 38 classes on unseen 12,784 test images. Several other CNN-based classifiers, including DenseNet-201 [21,22], DenseNet-121 [22,25,29,33], ResNet-50 [21,30,33], and VGG-16 [26,32,33] were also trained on the same samples. The confusion matrix of each model was generated and combined, and their corresponding true positive rates were compared with the proposed model; the comparison is shown in Figure 8 We calculate the precision, recall, and F1 score of the proposed PDD-Net, as shown in Table 3, for all 38 classes of the PlantVillage benchmark dataset.…”
Section: Plantvillagementioning
confidence: 99%
See 2 more Smart Citations
“…The models were trained and tested on two sets of data with the best results from CNN, with an accuracy of 96.9% and a computational time of 11.8 minutes. Tariq et al (2022) proposed a DL framework for classifying fruit diseases using transfer learning and a harmonic threshold‐based genetic algorithm. The method achieved an accuracy of 99% when tested on the PlantVillage data set (https://www.kaggle.com/datasets/emmarex/plantdisease).…”
Section: Introductionmentioning
confidence: 99%